2016
DOI: 10.4172/2155-9899.1000454
|View full text |Cite
|
Sign up to set email alerts
|

AR-12 Inhibits Chaperone Proteins Preventing Virus Replication and the Accumulation of Toxic Misfolded Proteins

Abstract: CommentaryAlthough originally thought to be an inhibitor of PDK-1, OSU-03012 (AR-12) was shown in 2005 not to primarily act as a PDK-1 inhibitor in its ability to radio-sensitize tumor cells [1,2]. Subsequently it was shown that the primary mechanism by which AR-12 killed tumor cells was via the PKR-like endoplasmic reticulum kinase (PERK) -dependent induction of endoplasmic reticulum stress signaling [1][2][3]. ER stress signaling in turn promoted a toxic form of autophagy resulting in a necroptotic form of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Previous work has disputed the designation of OSU-03012 as a PDPK1 inhibitor and identified that cell death following treatment with OSU-03012 occurred via induction of ER-stress signaling 77 . Additional studies identified changes in abundance and stability of heat shock proteins (HSPs) following OSU-03012 treatment and suggested that HSPs were targets of OSU-03012 78 . Our dataset identified a significant correlation with HSP90 (HSP90AB1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has disputed the designation of OSU-03012 as a PDPK1 inhibitor and identified that cell death following treatment with OSU-03012 occurred via induction of ER-stress signaling 77 . Additional studies identified changes in abundance and stability of heat shock proteins (HSPs) following OSU-03012 treatment and suggested that HSPs were targets of OSU-03012 78 . Our dataset identified a significant correlation with HSP90 (HSP90AB1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has disputed the designation of OSU-03012 as a PDPK1 inhibitor, and identified that cell death following treatment with OSU-03012 occurred via induction of ER-stress signaling 71 . Additional studies identified changes in abundance and stability of heat shock proteins (HSPs) following OSU-03012 treatment, and suggested that HSPs were targets of OSU-03012 72 . Our dataset identified significant correlation with HSP90 (HSP90AB1, Figure 5F) in support of this hypothesis.…”
Section: The Proteome Of All Cell Lines Echoes Distinct States In B-cell Differentiationmentioning
confidence: 99%
“…Additional data demonstrate that the mechanism was autophagy induction, as with bacteria and fungi. For the peer-reviewed companion paper, see Booth et al [38].…”
Section: Wo/2017/144583mentioning
confidence: 99%